The Impact of Product Quality, Price and Promotion on Axis Card Purchase Decisions On Students In Padang City - Aminar Sutra Dewi; Putri Reno Intan (Marketing Management Studies, 2021)
During the Covid-19 pandemic, it began in March and until now people have spent more time at home playing on their gadgets and of course they want smooth communication so that their intended goals are achieved. Purchasing decisions on the use of a simcard must be right, and one of the sim cards that are being targeted by students or teenagers today is the Axis card. This study aims to test purchasing decisions on product quality, to test purchasing decisions on prices, to testing purchasing decisions on promotions, sampling method using saturated sampling technique as many as 78 samples, using multiple linear regression testing. The results showed that purchasing decisions have a positive and significant effect on product quality, purchasing decisions have a positive and significant effect on prices, and purchasing decisions have a positive and significant effect on promotions.